ANALISIS DAMPAK GAYA TUMBUKAN MELALUI PERUBAHAN BENTUK SEGI CRUSH INITIATOR PADA STRUKTUR TAILOR-WELDED BLANK - Felix Dionisius; I'ah Wasiah; Jos Istiyanto; Mohammad Malawat; Bobi Khoerun (P3M Politeknik Negeri Indramayu, 2019)
Tailor-welded blank (TWB) structure is one of the vehicle component models used in vehicle parts. In addition, these structures can be used in crashworthiess technology which can reduce injuries during a collision.. The structure of a vehicle that has greater strength can cause passengers to be thrown from the passenger compartment. This paper discusses the effect of faceted holes such as square, hexagonal and octagonal as crush initiator mounted on TWB which results in a maximum impact force (Fmax). The smallest maximum impact force is the criteria achieved from this study. The method used experimental quasi-static loading of the actuator speed of 0.5 mm/s to achieve 9.5 mm of deformation. TWB was made from plate formation with a process of stamping to spot weld. The result showed that the maximum impact force has an increase directly proportional to the addition of the shape of the crush initiator in the amount of 14.633 kN to 18.705 kN. From these results, it can be seen a square hole as best design in obtaining the smallest maximum impact force.